Scientific criticism of “DNA criminal investigation – DNA database, mandatory DNA collection and time limit for data retention” - Notes on the unconstitutionality of Law 12.654/2012 - Garrido, Rodrigo Grazinoli (2018)
This scientific criticism was based on what was proposed by the article “DNA criminal investigation – DNA database, mandatory DNA collection and time limit for data retention” - Notes on the unconstitutionality of Law 12.654/2012”, in the search to offer doctrinal and empirical evidences that allowed to expand the academic dialogue on the implantation of the National Database of Genetic Profiles (BNPG). For that, we conducted exploratory and qualitative research, developed from documentation of doctrine, empirical work, judgments and rules related to the Brazilian and foreign databases. It is possible to recognize the possibility of using different references from the one presented by the article in question and, thus, the scope of contrary conclusions, particularly regarding the offense to the principle nemo tenetur is detegere in the application of Law 12,654 / 2012. Furthermore, important limitations in relation to the reduction of crime rates and the increase in DNA databases need to be emphasized.